Hubungan Pengetahuan Dan Sikap Ibu Hamil Tentang Pemanfaatan Buku KIA Di Desa Rambah Tengah Barat Wilayah Kerja Puskesmas Rambah - Latifah, Ermiza; dinda, Dinda mutia khairani; bewelli, yuyun; fitria, Rahmi (Maternity and Neonatal : Jurnal Kebidanan, 2022)
The MCH handbook is one of the maternal and child health guidebooks which is an important means of communication and information dissemination for mothers and families and the community regarding maternal and child health services (MCH). Maternal and Child Health Program (MCH) is a program to reduce MMR and IMR. As well as essential obstetric services at community health service centers. The correct application of the MCH handbook will have an impact on increasing the knowledge of mothers and families about maternal and child health, mobilizing and empowering the community to live healthy lives. pregnancy, childbirth, and children aged 5 years on the use of maternal and child health books (KIA). The use of the MCH Handbook is one of the strategies for community empowerment. This program is intended as an effort to improve maternal and child health services. The purpose of this study is to determine the relationship and attitudes of pregnant women regarding the use of MCH books in Rambah Tengah Barat Village. cross sectional time. The sample in this study amounted to 34 people, the sampling technique was total sampling. The data collection tool was using a questionnaire. The data analysis test was the chi-square test. The results of the study from the chi-square test obtained a value of p = 0.001 which means that there is a relationship between knowledge and attitudes towards the use of MCH books. Keywords: Knowledge, Attitude, Utilization of MCH